PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON EQUITY (ROE) PADA PT INDOMOBIL SUKSES INTERNASIONAL TBK PERIODE 2013-2022 - Sultan Alam Purba; I Gede Marendra (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) on PT Indomobil Sukses Internasional Tbk for the 2013-2022 period. The research uses 2 (two) independent variables, namely Current Ratio (CR) and Debt to Equity Ratio (DER) and 1 (one) dependent variable, namely Return on Equity (ROE). The research methodology uses the SPSS Version 26 application. Apart from that, the tests used in this research are the Classic Assumption Test, Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Determination Test, and Hypothesis Test. Based on test results on variables with 11 years of data. The Multiple Linear Regression Test Equation is Y = -21.521 + 0.170X1 + 0.025X2. Based on the results of the t test, it was obtained that tcount for CR was 1.114 < ttable 2.365 and the value of Sig. 0.298 > 0.05 means there is no partial significant influence between CR and ROE. and tcount of DER is 0.245 < ttable 2.365 and the Sig value. 0.245 > 0.05, which means there is no partial significant influence between DER and ROE, in the simultaneous test the CR and DER variables do not have a significant influence on ROE with Fcount greater than Ftable (0.714 < 4.74).